KEMAMPUAN MENULIS PARAGRAF EKSPOSISI BERDASARKAN TEKS WAWANCARA SISWA KELAS X SMA NEGERI 1 RANAH PESISIR KABUPATEN PESISIR SELATAN - Lispiana, Tati; Mana, Lira Hayu Afdetis; Nisja, Indriani (Pendidikan Bahasa Indonesia, 2014)
This study have some background, the first, the lack abilities of students to explore their ideas, concepts, thoughts, that would be written into paragraph. The second, the lack abilities of students to write exposition paragraph based on the interview text. The third, the lack abilities of students use the right spelling. This research purposes to describes the ability in writing exposition paragraph based on the interview text of the senior high school students grade X in SMA N 1 Ranah Pesisir Kabupaten Pesisir Selatan. The kind of this research is quantitative reseach. The population is the students grade X SMA N 1 Ranah Pesisir Kabupaten Pesisir Selatan with the total number of students 40, by using the proportional random sampling technique. Taking the sampel based on the number of students in each classes. Analysing the data was done by some steps: The first, reading the compositions that were written by the students. The second, Scoring of the expositions were written by the students. The third, changing the score becoming mean score. The fourth, describing, how was the students abilityes level in writing exposition paragraph based on the interview text. The fifth, gualifying how was the students abilities in writing exposition paragraph based on the interview text. The sixth, discussing the result of the data analysis result and the discussion. The result of data analysis showed that the ability of writing eksposition paragraph of the students based on the interview text were classified into excellent, while the main score was 89,33, where as on the level of mastering is 86-95% in the scale of 10.